2013
DOI: 10.3390/ijms141020414
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 42 Microsatellite Markers from Poison Ivy, Toxicodendron radicans (Anacardiaceae)

Abstract: Poison ivy, Toxicodendron radicans, and poison oaks, T. diversilobum and T. pubescens, are perennial woody species of the Anacardiaceae and are poisonous, containing strong allergens named urushiols that cause allergic contact dermatitis. Poison ivy is a species distributed from North America to East Asia, while T. diversilobum and T. pubescens are distributed in western and eastern North America, respectively. Phylogreography and population structure of these species remain unclear. Here, we developed microsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…For example, side chains of urushiols from T. radicans and T. pubescens have C15 and C17 carbon atoms, respectively, with 0, 1, 2 or 3 double bonds in the side chain (Hsu et al . ). In this regard, the Schinopsis species showed interspecific differences in saturation and length of the side chain as well as in the hydroxyl substitution of the aromatic ring.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, side chains of urushiols from T. radicans and T. pubescens have C15 and C17 carbon atoms, respectively, with 0, 1, 2 or 3 double bonds in the side chain (Hsu et al . ). In this regard, the Schinopsis species showed interspecific differences in saturation and length of the side chain as well as in the hydroxyl substitution of the aromatic ring.…”
Section: Discussionmentioning
confidence: 97%
“…ND, not detected. bonds in the side chain (Hsu et al 2013). In this regard, the Schinopsis species showed interspecific differences in saturation and length of the side chain as well as in the hydroxyl substitution of the aromatic ring.…”
Section: Discussionmentioning
confidence: 99%
“…Dispersal and vicariance events that exposed geographic isolation among taxa might be due to the land bridge submergence (Chiang et al, 2009;Chiang et al, 2013;Ge et al, 2012;Ge et al, 2015;Hsu et al, 2013) in Sunda Shelf and Sunda Super Island during the Pleistocene ( Figure 5 and Table 2) (Guo et al, 2015;Tsai et al, 2015). Cenozoic collision accompanied by a cyclical climate (glacial oscillations) caused by the fragmentation of the Sunda Super Islands (de Bruyn et al, 2014).…”
Section: Biogeography and Evolutionary Trendsmentioning
confidence: 99%
“…Microsatellite markers are simple sequences repeat (SSRs) consisting of 1-6 nucleotides in length (motifs) and can be found in genomes of all prokaryotes and eukaryotes [7]. During the past decades, microsatellite markers, due to the high level of polymorphism, high abundance, co-dominance, selective neutrality and transferability across species [8][9][10][11][12], have been widely applied to a variety of biological researches, such as population genetics, gene flow, phylogenetics, and conservation genetics. A latest study has reported 18 polymorphic loci isolated from Angelica sinensis [13].…”
mentioning
confidence: 99%